Size Stabilizers in Two-electrode Synthesis of ZnO Nanorods - Korol, R.V.; Yanchuk, O.M.; Marchuk, O.V.; Orlov, V.F.; Moroz, I.A.; Vyshnevskyi, O.A. (Physics and Chemistry of Solid State, 2021)
We modify and optimize a cheap, simple and effective synthesis of zinc oxide nanosized particles by electrodeposition. The core method encompasses the synthesis of ZnO product on the soluble zinc anode of the two-zinc-electrode cell emerged in aqueous NaCl. Resulting particles have the shape of cocoa fruit, thick in the middle and sharp at the edges. They have uniform shape, but broad size distributions with most of the ZnO product 1-2 µm long and 0,5-0,7 µm thick. Thus, auxiliary stabilizers are added to aqueous phase to reduce the size and narrow its distribution in the target product. Here we present the size stabilizing action of four successful stabilizers: urea, polyvinyl alcohol, Triton x-100 and Atlas G3300. All of them reduce particle size and polydispersity. An anionactive surfactant atlas is the most effective, giving an order of magnitude nanorod size reduction.